Are serum hepcidin levels chronically elevated in collegiate female distance runners? - Ma, X.; Patterson, K. J.; Gieschen, K. M.; Bodary, P. F. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
The prevalence of iron deficiency tends to be higher in athletic populations, especially among endurancetrained females. Recent studies have provided evidence that the iron-regulating hormone hepcidin is transiently increased with acute exercise and suggest that this may contribute to iron deficiency anemia in athletes. The purpose of this study was to determine whether resting serum hepcidin is significantly elevated in highly trained female distance runners compared with a low exercise control group. Due to the importance of the monocyte in the process of iron recycling, monocyte expression of hepcidin was also measured. A single fasted blood sample was collected midseason from twenty female distance runners averaging 81.9 ± 14.2 km of running per week. Ten age-, gender-, and BMI-matched low-exercise control subjects provided samples during the same period using identical collection procedures. There was no difference between the runners (RUN) and control subjects (CON) for serum hepcidin levels (p = .159). In addition, monocyte hepcidin gene expression was not different between the two groups (p = .635). Furthermore, no relationship between weekly training volume and serum hepcidin concentration was evident among the trained runners. The results suggest that hepcidin is not chronically elevated with sustained training in competitive collegiate runners. This is an important finding because the current clinical conditions that link hepcidin to anemia include a sustained elevation in serum hepcidin. Nevertheless, additional studies are needed to determine the clinical relevance of the well-documented, transient rise in hepcidin that follows acute sessions of exercise.